“When the Seagulls Cry”? Biobanks and Local Tradition - Olejarz, Sylwia (Current Problems of Psychiatry, 2011)
This article aims to present the proposal which demonstrates – on the example of a specific country - how local tradition can help to adopt “globalized” initiatives such as the idea of biobanks.